Tobacco intercropping enhances soil fertility by improving synergic interactions between soil physicochemical and microbial properties - Gu, Kaiyuan; Liu, Xianglu; Liu, Ming; Wei, Xu; Li, Juan; Hu, Yanxia; Jiang, Yonglei; Chen, Yi; Wang, Dexun; Yang, Yanming; Su, Jiaen; Wang, Longchang (Frontiers in Microbiology, 2025)
IntroductionIntercropping tobacco with other crops has been shown to upregulate soil health by fostering synergistic interactions between physicochemical and microbial properties. This study aims to evaluate the impact of intercropping on physicochemical attributes, rhizospheric microbial community, and functional dynamics of soil cultivated with tobacco plants.MethodsA field experiment was comprised with five treatments, such as tobacco monoculture (TT), soybean monoculture (SS), maize monoculture (MM), tobacco–soybean intercropping (TS), and tobacco–maize intercropping (TM). Soil nutrients observed, while bacterial and fungal community profiles were assessed through high-throughput sequencing targeting the 16S rDNA and ITS hypervariable regions. Microbial interactions and network resilience were assessed through co-occurrence network analysis.ResultsIntercropping significantly improved the soil nutrient properties. Compared with tobacco monoculture (TT), the tobacco–soybean intercropping (TS) treatment enhanced cation exchange capacity (CEC), total nitrogen (TN), available phosphorus (AP), and available potassium (AK) by 13.9, 13.9, 43.8, and 129.1%, respectively. Tobacco–maize intercropping (TM) enhanced CEC (26.7%) and AK (9.7%). Both intercropping models significantly increased bacterial species richness in tobacco soil, whereas fungal diversity was more pronounced under monoculture conditions. Intercropping favored the proliferation of Proteobacteria and Basidiomycota, while concurrently suppressing Ascomycota. Tobacco–maize intercropping specifically augmented nitrifying bacteria and Actinobacteria, while tobacco–soybean intercropping predominantly facilitated the recruitment of symbiotic fungi. Intercropping intensified microbial network complexity and modularity, upregulate ecosystem resilience to disturbances. Mantel analysis indicated that the bacterial community structure was primarily influenced by soil pH, whereas fungal communities exhibited strong combinations with available potassium and phosphorus.DiscussionIntercropping systems substantially improved soil ecological functionality by modulating microbial community composition and nutrient dynamics. Tobacco–maize intercropping reinforced soil ecosystem stability through enrichment of functional microorganisms and optimization of community architecture, while tobacco–soybean intercropping leveraged nitrogen fixation by legumes to augment nitrogen availability and facilitate the establishment of nitrogen-cycling microbes, demonstrating superior efficacy in enhancing soil fertility. These findings suggest that tobacco intercropping can be sustainable agricultural strategy to maintain soil health and productivity in the era of climate change.